From pollution to resource: advancing swine waste treatment in the USA - Aneja, Viney P.; Longest, Ryke; Vanotti, Matias B.; Szogi, Ariel A.; Reddy, Gudigopuram B. (Frontiers in Sustainable Food Systems, 2024)
Concentrated animal feeding operations (CAFOs) have led to environmental challenges, specifically waste management. Swine CAFOs generate large amounts of waste, requiring proper treatment to avoid air and water pollution. Conventional waste management technologies, such as lagoon and spray field systems, do not prevent air and water pollution impacts. Research for the past few decades led to recommendations for waste treatment technologies superior to lagoons and spray fields. Private environmental sustainability initiatives focused on reducing greenhouse gas emissions in the food supply chain have implemented biogas digester projects for capturing methane in covered swine lagoons to reduce greenhouse gas emissions. However, research indicates that methane capture alone does not solve the broader pollution issues associated with lagoon and spray field systems still in use at these CAFOs to dispose of digested effluents. The Environmentally Superior Technologies (EST) initiative in North Carolina set public standards to eliminate waste discharge, reduce atmospheric emissions, and control odors and pathogens. Research has confirmed that technologies coupling solids separation with water treatments to remove volatile organic carbon, pathogens, and reactive forms of nitrogen can meet EST standards. A designated EST—the Super Soil System—substantially reduced odor by 99.9%; pathogens by 99.99%, nutrients (phosphorus and nitrogen) by >90%, and heavy metals (cooper and zinc) by 99%. The ammonia emissions were reduced by 94.4% for the warm and 99.0% for the cool season with respect to a conventional lagoon system. Corresponding greenhouse gas emission reductions were 96.7%. Components of designated EST can be applied to retrofit covered lagoons and anaerobic digestion systems with significant environmental benefits. Recommendations are proposed, based on the collective experience with EST and current trends in animal production concentration, for environmentally safe technologies to handle excess manure produced in the USA.